Congenital Heart Defects and Ciliopathies Associated With Renal Phenotypes - George C. Gabriel; Gregory J. Pazour; Cecilia W. Lo (Frontiers in Pediatrics, 2018)
Congenital heart disease (CHD) is one of the most common birth defects, and recent studies indicate cilia-related mutations play a central role in the genetic etiology of CHD. As cilia are also known to have important roles in kidney development and disease, it is not surprising that renal anomalies were found to be enriched among CHD mutant mice recovered in a large-scale mouse forward genetic screen. Indeed 42% of mutations identified to cause both CHD and renal anomalies were cilia-related. Many of these cilia mutations comprise cilia transition zone or inversin compartment components, consistent with the known role of these cilia proteins in a wide variety of ciliopathies. The high prevalence of CHD with congenital anomalies of the kidney and urinary tract (CAKUT) observed in mice was also corroborated with clinical studies that showed 20–30% of CHD patients have renal anomalies. Together these findings suggest CHD patients may benefit from early screening for renal anomalies to allow early diagnosis and intervention to improve outcome for this vulnerable patient population.